MAQASID AL-SHARIAH: SOME PRELIMINARY DISCUSSIONS - Wani, Gowhar Quadir (Universitas Islam Indonesia, 2018)
Maqasid al-Syariah is a potent tool to understand Syariah – the Devine path leading to the welfare of humanity in a comprehensive way – in a rational, purpose-oriented, and humanistic way. However, due to some historical factors like fossilization of the Islamic jurisprudence into various schools (mazahib) and the closure of the gate of ijtihad, etc. the maqasid remained a somewhat neglected theme in Islamic legal theory.